Organ Transplants: Inadequate Social Responsibility to be Resolved - Cantarovich F (Achievements and Challenges of Medicine and Medical Science Vol. 8, 2024)
Since the mid-twentieth century, after a long journey in time, organ and tissue transplants offer unlimited health and wellness potential for the benefit of society. Dying unfairly in the long lists of transplants is the difficult current alternative for thousands of patients waiting for a future life opportunity. From the beginning of the fascinating era of organ transplantation, this cruel reality permanently censured our society. Paradoxically, surgical techniques in this regard and therapeutics for prevention and/or rejection of the transplanted organ have progressively advanced over time. On the other hand, particularly in the case of end-stage renal failure, the national budgets for hemodialytic treatments are undoubtedly a serious economic crisis probably the therapeutic improvement of kidney transplantation, will be the potential solution. Society's response to organ donation, especially in the case of a deceased donor, has not followed this successful therapeutic solution of transplantation. The paradigm of recovering life through the death of another human being is a difficult metaphor to be interpreted by people. The objective of this article is to analyze the possible causes of this crisis and propose a change in the strategy of current educational programs with respect to organ donation, given its statistical inertia to improve public behavior. The main intention is to suggest the review of the global planning of donation and transplant education, seeking to achieve a clear public knowledge of the critical existential dilemma of our time: to recover health and life thanks to the transplantation of organs and tissues. In conclusion, this simple proposal might be a possible initial way to solve this serious medical, political and social dilemma that globally affects us. Trying this path will certainly not be difficult and trying it can be a valid effort that consciously elaborates on the possibility that society deserves to be tested for the benefit and respect of people.